Philosophical aspects of the truth in the Orazione XV of Caterina da Siena - Griva, Anna (Dia-noesis: A Journal of Philosophy, 2025)
This article will focus on the references to truth (verità) in the work Orazioni by the 14th-century Italian mystic, theologian, and philosopher Caterina da Siena. Within the dense and philosophically structured reflections of the Orazioni, truth is a term that recurs and acquires fundamental importance for understanding the worldview of the Italian philosopher. It can also be seen within a broader framework of philosophical perspectives on the relationship between parts and the whole, as well as on the participation of humans in the cosmic unity. We will particularly focus on Orazione XV, in which a more complete presentation of the term truth is provided through a clear reasoning process.